Lords of Terrorism in the Contemporary Novel - Abu Adel, Mohammed Ahmed (Journal of Humanities & Social Sciences, 2020)
This paper explores the psychological secrets of the terrorist character in the novel “Confessions of a Terrorist”, which rebels against the stereotypical view which is unable to grasp and control the phenomenon of terrorism to eliminate it, or at least reduce its dangers. This novel has a unique view of the character of the terrorist which is showed through a new and different perspective. The novelist tries to expose the failure of traditional strategies that are ineffective in stopping the growth and spread of terrorism. The language of excessive violence in dealing with terrorists, its use under the pretext of getting rid of the opponents and the lack of sincere intention are counterproductive, usually forgetting the language of dialogue as a means to finding a common ground to find a solution. This novel differs from the books and novels published in non-Arabic languages because it adopts a neutral and non-politicized view. Western societies need to know the reality of terrorism revealed by the novel. The reason is that these societies are prejudiced by western media films and what they hear and watch on TV. Therefore, this paper is keen to truly examine the ideological content that the novel poses for this kind of terrorism. - The paper is divided into three main axes: 1. Arab Terrorist from a westerner standpoint. 2. Western terrorism from the standpoint of an Arab Terrorist.3. Culture of dialogue and tolerance.